Runoff and soil erosion response to clear cutting period of acacia plantation in a headwater mountain of Vietnam - Dung, Bui Xuan; Kim, Thanh Do Thi (Research and Social Study Institute, 2021)
This study evaluated the responses of runoff and soil erosion to a clear-cutting period of Acacia plantation in a headwater mountain. Two plots with 15m2 (3m width*5m length) were installed in a headwater mountain of Hoa Binh, Vietnam. Plot 1 remained untreated as the control plot, while plot 2 was clear-cutting in March 2019. Runoff and soil erosion was observed from April to September 2018 for the pre-cutting period with 55 storm events and from March to May 2019 for the post- cutting period with 15 storms-events. Observed data was examined the effects of the cutting period by using paired-plot analysis that compared the control plot and the treatment plot. The main results included: (1) Surface runoff after clear-cutting increased statistical significantly from 0.18 mm storm-1 (corresponding to 0.38 %) to 0.26 mm storm-1 (corresponding to 0.56 %). Paired- plot analysis showed the increase of surface flow is 81.14% after cutting; (2) Soil erosion increased statistically significant after clear-cutting from 228.44 g/storm to 309.27 g/storm on average, the amount of soil erosion due to treatment effect increased 33.1 %. The increase of runoff and soil erosion is quite high after the cutting period. This suggests that plantation management practices to control runoff and soil erosion in the headwater basin are necessary for Vietnam.